Male Infertility: Causes and Current Developments in Diagnostic Work-Up - Kahyaoğlu, İnci; Yılmaz, Nafiye (Gynecology Obstetrics & Reproductive Medicine, 2013)
Male factor infertility gained importance during the last two decades in the infertility work-up and necessitates the revision of basal semen analysis parameters. Diagnostic evaluation of the male begins with a detailed history, physical examination and a semen analysis. Hormonal and genetic evaluation is done if indicated. The expeditious progress in the assisted reproductive techniques, highlight the importance of genetic testing in the evaluation of the male patient and in cases like azoospermia in which the prognosis may change the treatment protocol.